2017
DOI: 10.1088/1361-6463/aa949e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of magneto-optical effects by a single 1D all dielectric resonant grating

Abstract: We demonstrate theoretically the enhancement of the four first-order magneto-optical effects using an all-dielectric 1D resonant grating. The modeled structure was designed for the Faraday effect at normal incidence at a wavelength of 1.55 µm for which the calculated improvement is shown to be one hundred times the off-resonance values. At 1° incidence, polar and longitudinal Kerr effects were also improved, showing polarization rotations up to 14°. For the same incidence conditions, transverse magneto optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…A possibility of the enhancement of the MO effects by one free-space dielectric grating has been theoretically demonstrated. [33,34]. The first experimental results were obtained for a highdielectric-index impregnated grating template, [33] with an MNP-doped mineral sol-gel.…”
Section: Magneto-optical Properties and Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…A possibility of the enhancement of the MO effects by one free-space dielectric grating has been theoretically demonstrated. [33,34]. The first experimental results were obtained for a highdielectric-index impregnated grating template, [33] with an MNP-doped mineral sol-gel.…”
Section: Magneto-optical Properties and Devicesmentioning
confidence: 99%
“…The corresponding simulated structure took into account the dispersion of the refractive index of the photostructurable nanocomposite. MO modelling was performed using a custom RCWA code, [33] taking into account the entire permittivity tensor. [35] The Fourier modal method (FMM) or RCWA is the most suitable numerical method for analyzing the interactions of electromagnetic waves with periodic diffractive structures.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, all-dielectric nanostructures 39 are promising in the sense that resonance high quality factors and transparency might be combined with high magnetooptical modulation efficiencies. The 1D 40 , 41 and 2D 42 all-dielectric magnetic gratings and nanoparticles 43 were numerically predicted to increase some magneto-optical effects. However, fabrication of such complex shapes is challenging, and, on the other hand, the resulting optical response would be significantly affected not only by the material losses, but also by the surface roughness and fabrication inaccuracies that are neglected in these theoretical studies 40 43 .…”
Section: Introductionmentioning
confidence: 99%
“…The 1D 40 , 41 and 2D 42 all-dielectric magnetic gratings and nanoparticles 43 were numerically predicted to increase some magneto-optical effects. However, fabrication of such complex shapes is challenging, and, on the other hand, the resulting optical response would be significantly affected not only by the material losses, but also by the surface roughness and fabrication inaccuracies that are neglected in these theoretical studies 40 43 . Although recent experimental studies 44 reveal the enhancement of TMOKE in 1D all-dielectric gratings, it is still observed only for p-polarized illumination and completely vanishes for s-polarized light.…”
Section: Introductionmentioning
confidence: 99%